A Cantor Fractal Based Printed Monopole Antenna for Dual-band Wireless Applications - Mohammed R. Hussan (Engineering and Technology Journal, 2016)
Cantor fractal geometry and its variants are found attractive for microwave antenna designers seeking for compact size multiband antennas. This paper presents the design of a new microstrip fed printed monopole antenna for use in dual-band wireless applications. The radiatingelement of the monopole antenna is in the form of Cantor fractal geometry of the second iteration as applied on rectangular patch. The monopole radiating element has been etched on a substrate with relative permittivity of 4.4 and 1.6 mm thickness and is fed with a 50 ohm microstrip line. A reduced ground plane has been etched on the reverse side of the substrate. Modeling and performance evaluation of the proposed antenna have been carried out using the commercially available EM simulator, IE3D. Simulation results reveal that the proposed antenna offers dual-band resonant behavior with –10 dB impedance bandwidths and radiation characteristics suitable for almost most of the recently available services in the 1-6 GHz range. A parametric study has been carried out to explore the effect the aspect ratio of the proposed antenna radiating element on its performance. The study reveals that the radiating element aspect ratio has a considerable effect on the coupling of the two resonant bands. Besides the simple design, the antenna offers reasonable radiation characteristics. Simulated–10 dB impedance bandwidths for the lower and the upper resonant bands are (2.30–2.84 GHz) and (5.56–6.01 GHz) respectively. This makes the proposed antenna suitable to cover numbers of operating bands of the wireless communication systems (2.4 GHz-Bluetooth, 2.4 GHz ISM, 2.5/5.8 GHz-WLAN, 5.8 GHz-ITS).